Monitoring and assessment of rocky reefs and maërl communities in the Special Conservation Area “SCA - Underwater Valleys of the Mazarrón Escarpment” (SE Iberian Peninsula, Western Mediterranean) - Bellido, Jose M.; Terrones, Beatriz; Muñoz, Ana (Frontiers in Ocean Sustainability, 2026)
Rocky reef ecosystems and maërl communities have a great ecological importance. However, as most of these habitats are present in shallow water near shore, they are particularly vulnerable to the effects of human activities. The main goal of this research is to improve the knowledge on maërl communities and reefs within the Special Conservation Area (SCA) “Underwater Valleys of the Mazarrón Escarpment”, in southeast Spain. An intensive sampling of benthic habitats between 20 and 300 m depth by two coastal and two oceanographic surveys was conducted during 2022 and 2023. We made use of towed sledge and ROVs as main sampling methodologies, although some other benthic dredges were also utilized (shipek dredge, beam trawl and rock dredge). Results show a high taxonomic richness of megabenthic species. Currently approximately 400 taxa have been identified to the lowest possible taxonomic level, with a particular focus on the habitats of community interest “rocky reefs - 1170” (Alcyonium acaule, Alcyonium palmatum, Leptogorgia sarmentosa, Cerianthus membranaceus among others) and maërl communities (Lithothamnion spp., Mesophyllum spp., Phymatolithon calcareum, Peyssonnelia rosa-marina among others). Then we constructed an accurate habitat zoning and new bionomic cartography with a finer spatial resolution for the habitats of rocky reefs and maërl communities. Finally, we estimated a set of specific ecological indicators, which allow evaluating their conservation status, their monitoring over time as well as their spatio-temporal evolution.